INVESTMENT VIABILITY OF COLD STORAGE INFRASTRUCTURE FOR AGRICULTURAL PRODUCE IN TELANGANA STATE - Y. RADHA, SHRUTI NAIR, SEEMA and (The Journal of Research, PJTSAU, 2017)
The eradication of poverty and hunger is the most important of the United Nations’ Millennium Development Goals. Post harvest storage solutions that could enable the deferred sale of horticultural produce would provide farmers with options to tide them over the crisis of low market prices during the harvest season and spread product supply in market over a wider period, thus, enabling remunerative returns.